Ninjin'yoeito Targets Distinct Ca2+ Channels to Activate Ghrelin-Responsive vs. Unresponsive NPY Neurons in the Arcuate Nucleus - Goswami, Chayon; Dezaki, Katsuya; Wang, Lei; Inui, Akio; Seino, Yutaka; Yada, Toshihiko (Frontiers in Nutrition, 2020)
Appetite loss or anorexia substantially deteriorates quality of life in various diseases, and stand upstream of frailty. Neuropeptide Y (NPY) in the hypothalamic arcuate nucleus (ARC) and ghrelin released from stomach are potent inducers of appetite. We previously reported that Ninjin'yoeito, a Japanese kampo medicine comprising twelve herbs, restores food intake, and body weight in cisplatin-treated anorectic mice. Furthermore, Ninjin'yoeito increased cytosolic Ca2+ concentration ([Ca2+]i) in not only ghrelin-responsive but ghrelin-unresponsive NPY neurons in ARC. The cellular lineage/differentiation of ghrelin-unresponsive neuron is less defined but might alter along with aging and diet. This study examined the occupancy of ghrelin-unresponsive neurons among ARC NPY neurons in adult mice fed normal chow, and explored the mechanisms underlying Ninjin'yoeito-induced [Ca2+]i increases in ghrelin-unresponsive vs. ghrelin-responsive NPY neurons. Single ARC neurons were subjected to [Ca2+]i measurement and subsequent immunostaining for NPY. Ghrelin failed to increase [Ca2+]i in 42% of ARC NPY neurons. Ninjin'yoeito (10 μg/ml)-induced increases in [Ca2+]i were abolished in Ca2+ free condition in ghrelin-responsive and ghrelin-unresponsive ARC NPY neurons. Ninjin'yoeito-induced [Ca2+]i increases were inhibited by N-type Ca2+ channel blocker ω-conotoxin in the majority (17 of 20), while by L-type Ca2+ channel blocker nitrendipine in the minority (2 of 23), of ghrelin-responsive neurons. In contrast, Ninjin'yoeito-induced [Ca2+]i increases were inhibited by nitrendipine in the majority (14 of 17), while by ω-conotoxin in the minority (8 of 24), of ghrelin-unresponsive neurons. These results indicate that ghrelin-unresponsive neurons occur substantially among NPY neurons of ARC in adult mice fed normal chow. Ninjin'yoeito preferentially target N-type and L-type Ca2+ channels in the majority of ghrelin-responsive and ghrelin-unresponsive neurons, respectively, to increase [Ca2+]i. We suggest ARC N- and L-type Ca2+ channels as potential targets for activating, respectively, ghrelin-responsive, and unresponsive NPY neurons to treat anorexia.